Kendali Tegangan Output Buck Converter Menggunakan Arduino Berbasis Simulink Matlab - Ari Anggawan; Muldi Yuhendri (Jurnal Teknik Elektro Indonesia, 2021)
The rapid development of technology to date has made many electrical and electronic equipment that require a direct current (dc) voltage source whose output voltage can be adjusted to the needs of the user. There are several direct voltage levels that are commonly used by electrical and electronic equipment. To get a direct voltage that can be used for various equipment, a direct voltage source that can be varied according to need is required. One way to convert a dc voltage source to a lower dc voltage source is by using a buck converter circuit. This study proposes a buck type direct current converter is porposed to use the Arduino uno as a PWM signal generator circuit to control to control the 24 volt input voltage. The converter output voltage regulation is implemented through a potentiometer and Arduino programming using the simulink Matlab. In this research, a buck converter is tested with output voltage feedback so that the output voltage remains stable. The result of the test that have been carried out show that the buck converter designed in this study has worked well in accordance with objectives. This can be seen from the buck converter output voltage that is in accordance with the reference voltage using a potentiometer that is included in the simulink Matlab program.